1986
DOI: 10.1084/jem.163.6.1589
|View full text |Cite
|
Sign up to set email alerts
|

Newcastle disease virus-infected splenocytes express the proopiomelanocortin gene.

Abstract: Infection of murine splenocytes with Newcastle disease virus results in expression of the proopiomelanocortin gene as determined by dot and northern blot analysis of total cellular and poly(A)+ cytoplasmic RNA. These data provide the first evidence that the precursor protein for adrenocorticotropin and beta-endorphin can be synthesized by lymphoid cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0
1

Year Published

1987
1987
2011
2011

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 154 publications
(37 citation statements)
references
References 25 publications
(14 reference statements)
1
35
0
1
Order By: Relevance
“…Fortunately, individuals such as Kavelaars et al reproduced and extended many of our initial findings [12]. Moreover, Westly et al [13] together with John Funder's group [14] and others [15,16] provided a firm molecular foundation for our initial observations and predictions by demonstrating POMC mRNA is present in immune cells. In spite of these findings, the authenticity of the peptides continued to be questioned [17].…”
Section: Discovery Of Neuropeptides/ / Neurotransmitters In the Immunmentioning
confidence: 66%
“…Fortunately, individuals such as Kavelaars et al reproduced and extended many of our initial findings [12]. Moreover, Westly et al [13] together with John Funder's group [14] and others [15,16] provided a firm molecular foundation for our initial observations and predictions by demonstrating POMC mRNA is present in immune cells. In spite of these findings, the authenticity of the peptides continued to be questioned [17].…”
Section: Discovery Of Neuropeptides/ / Neurotransmitters In the Immunmentioning
confidence: 66%
“…IR-␤-EP is also present in lymphocytes (56) and macrophages (20). POMC mRNA transcript has been identified in splenic lymphocytes (57,58). Both acetylated and nonacetylated ␤-EP are produced in splenic lymphocytes (20).…”
Section: Figurementioning
confidence: 97%
“…At first, those peptides were assumed to be related to interferon-␣, which was disproved later (for review, see Busch-Dienstfertig and . Two groups simultaneously demonstrated the presence of full-length POMC mRNA encoding all three exons in immune cells (Lolait et al, 1986;Westly et al, 1986). Many other studies in leukocytes, however, described only truncated POMC mRNAs lacking the 5Ј untranslated region from the first and the signal sequence from the second exon (for review, see BuschDienstfertig and Stein, 2010).…”
Section: Opioid Peptides In Peripheral Sensorymentioning
confidence: 99%
“…The lack of the signal sequence omits the correct routing of the translation products and their processing to authentic POMC peptides in the regulated secretory pathway (Clark et al, 1990;Cool and Loh, 1994). Some studies found that the expression of full-length POMC mRNA was suppressed in mature unstimulated leukocytes, but could be induced under pathological conditions (Westly et al, 1986;Buzzetti et al, 1989;Ohta et al, 2000). Cabot et al (1997) and Sitte et al (2007) showed that POMC transcripts containing the signal sequence and subsequent END production are up-regulated in lymphocytes from rats with painful paw inflammation.…”
Section: Opioid Peptides In Peripheral Sensorymentioning
confidence: 99%